Socio-environmental topics from Social Work. The experience of the University of Atacama, Chile (2008-2023) - Mora-Castillo, María Alejandra; García-Carmona, Alfredo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The article analyzes the experience of the Social Work degree at the University of Atacama, Chile, on socio-environmental issues. In recent decades, the region has had an increase in conflicts in this area, which requires progress in training and research processes that are adapted to this context, in a region whose extractivist model has generated territorial disputes between various actors, with local communities being the most affected.Under a documentary research methodology with secondary sources, the main actions and products in the period 2008-2023 are described and analyzed, reflecting a sustained increase in the production of research on socio-environmental matters in the undergraduate career and from the attached professors.In conclusion, training in Social Work and the discipline must consider the relationship between society and nature as transcendental, especially when this training is carried out in and from extractivist contexts or zones of sacrifice where all the actors of the educational process are part of that context, living daily with the effects that this condition produces.